Pautas de redacción científica en ciencias de la salud: Título de la investigación : Guidelines for scientific writing in the health sciences: Title of the research study - Morales, Juan (2022)
The quality of the title of a scientific article reflects the quality of the article and can be decisive for the reading of the rest of the scientific paper. The descriptive or neutral title is the most recommended, also keep in mind the extension, syntax and grammatical structure. The writing of the title can be perfected throughout the research process, during the writing of the article, after the analysis and revision of the authors. It is important to consider the observations and/or suggestions after a critical review by a volunteer researcher and the reviewers or editors of the journals. It is also advisable to review the instructions of the journal to which you wish to submit. This paper has developed title types, guidelines, useful tips and title examples. Keywords: Biomedical Research; Research Design; Research Report; Publications (Source: MeSH, NLM).